Mutational analysis of EYA1, SIX1 and SIX5 genes and strategies for management of hearing loss in patients with BOR/BO syndrome. - Mee Hyun Song; Tae-Jun Kwon; Hui Ram Kim; Ju Hyun Jeon; Jeong-In Baek; Won-Sang Lee; Un-Kyung Kim; Jae Young Choi (PLoS ONE, 2013)
BACKGROUND: Branchio-oto-renal (BOR) or branchio-otic (BO) syndrome is one of the most common forms of autosomal dominant syndromic hearing loss. Mutations in EYA1, SIX1 and SIX5 genes have been associated with BOR syndrome. In this study, clinical and genetic analyses were performed in patients with BOR/BO syndrome focusing on auditory manifestations and rehabilitation. METHODS: The audiologic manifestations were reviewed in 10 patients with BOR/BO syndrome. The operative findings and hearing outcome were analyzed in patients who underwent middle ear surgeries. The modality and outcome of auditory rehabilitation were evaluated. Genetic analysis was performed for EYA1, SIX1, and SIX5 genes. RESULTS: All patients presented with mixed hearing loss. Five patients underwent middle ear surgeries without successful hearing gain. Cochlear implantation performed in two patients resulted in significant hearing improvement. Genetic analysis revealed four novel EYA1 mutations and a large deletion encompassing the EYA1 gene. CONCLUSIONS: Auditory rehabilitation in BOR/BO syndrome should be individually tailored keeping in mind the high failure rate after middle ear surgeries. Successful outcome can be expected with cochlear implantations in patients with BOR/BO syndrome who cannot benefit from hearing aids. The novel EYA1 mutations may add to the genotypic and phenotypic spectrum of BOR syndrome in the East Asian population.